Comparison of selected Swiss chard (Beta vulgaris ssp. cicla L.) varieties - R. Pokluda; J. Kuben (Horticultural Science, 2002)
Evaluation of 12 Swiss chard varieties (Beta vulgaris ssp. cicla L.) in field experiments was focused on the observation of morphological characteristics, yield and nutritional quality of leaves and stalks. The following mean parameters of all varieties were found: 86% field germination, plant weight 346 g, plant height 506 mm, stalk width 23 mm, 10 leaves per plant, and yield 35 t/ha. Mean content of vitamin C was 307 and 72 mg/kg of fresh matter (f.m.) in leaves and stalks, respectively. Potassium content was 4,198 and 4,848 mg, sodium amount was 2,101 and 966 mg, calcium content was 481 and 310 mg and finally magnesium content represented the levels of 361 and 113 mg/kg of f.m., always in leaves and stalks. Significant effects of plant height and plant leaf number on total plant weight were found. Plants with the mean weight of 400 g formed the widest stalks. In addition, a negative effect of higher yield on vitamin C and Ca stalk content was detected. An opposite effect was determined in Na and partially in Mg stalk content that simultaneously increased with higher yield levels. The variety Lucullus is still comparable with newer varieties such as Gator, Zürcher Gelber andCharlotte, which achieved good results among all tested varieties.